Dead wake : the last crossing of the Lusitania - Larson, Erik, 1954- (Crown Publishers, 2014)
The #1 New York Times best-selling author of In the Garden of Beasts presents a 100th-anniversary chronicle of the sinking of the Lusitania that discusses the factors that led to the tragedy and the contributions of such figures as President Wilson, bookseller Charles Lauriat and architect Theodate Pope Riddle.